Synthesis and study of the structure of copolymers of rarely crosslinked polyacrylic acid - Борденюк, О. Ю.; Капаціла, С. М.; Цикунков, С. С.; Надашкевич, З. Я.; Фігурка, Н. В.; Самарик, В. Я.; Bordenyuk, O. Y.; Kapatsila, S. M.; Tsykunkov, S. S.; Nadashkevych, Z. Ya.; Fihurka, N. V.; Samaryk, V. Ya. (Видавництво Львівської політехніки, 2024)
Досліджено взаємозв’язок структури кополімерів акрилової кислоти та N,N-метиленбісакриламіду від умов їх отримання. Встановлені оптимальні умови одержання полімерів із лінійною, деревоподібною та просторово-структурованою будовою макромолекул. Досліджено їх властивості, а саме густину, ступінь набрякання, гель-фракцію тощо. Показано, що кополімери із просторово-структурованими макромолекулами утворюють гідрогелі, ступінь набрякання яких істотно залежить від умов одержання. Для кополімерів, що утворюють гідрогелі, на основі залежностей густини та рівноважного ступеня набрякання визначено густину вузлів зшивок.

The effect of synthesis conditions on the structure of acrylic acid and N,N-methylene bisacrylamide copolymers has been investigated. Optimal conditions for the synthesis of polymers with linear, tree-like, and crosslinked macromolecular structures have been established. The properties of the synthesized polymers, namely density, degree of swelling, gel fraction, etc., were investigated. It has been shown that copolymers with crosslinked macromolecules form hydrogels, the swelling degree of which considerably depends on the synthesis conditions. For copolymers forming hydrogels, the density of crosslinking units was determined based on the dependence of the density and equilibrium swelling degree.
Синтез та дослідження будови кополімерів рідкоструктурованої поліакрилової кислоти
Keywords: акрилова кислота; кополімер; структура; гель- та золь-фракція; ступінь зшивки; acrylic acid; copolymer; structure; gel and sol fractions; crosslinking degree